Productive Zakat of Baznas Yogyakarta on the Growth of Micro Business - Agus Faisal; Irma Yuliani (Shirkah: Journal of Economics and Business, 2017)
This empirical study aims to determine the impact of the productive zakat, infaq and sadaqah (ZIS) on the growth of micro business and the welfare of mustahiq in Badan Amil Zakat Nasional (Baznas) branch of Daerah Istimewa Yogyakarta (DIY). Applying structural equation modeling partial least square (PLS SEM), it confidently aims to verify the factors that influence the mustahiq welfare. The data of the research had systematically gathered by distributing questionnaires to 50 respondents and analytically processed by SmartPLS 3.0. This paper found that the productivity of ZIS took significantly positive influence on the growth of micro business and the welfare of mustahiq. In other words, the financial capital given to mustahiq able to improve micro business through developing the employment.Â Keywords: zakat, infaq, sadaqah, micro business, SmartPLS, Baznas, Yogyakarta